Reproductive and productive efficiency in white and naturally colored Corriedale ewes (Research, Society and Development, 2022)
The objective of this study was to evaluate the influence of phenotype on the reproductive efficiency of sheep and the performance of lambs from birth to weaning. were used of 111 adult Corriedale ewes (54 natural colored and 57 white), kept in natural pasture, supplemented in the final third of gestation and grazed in improved natural pasture after birth. The matings were performed by artificial insemination and controlled mount. After birth, the lambs were weighed at mean intervals of 28 days and weaned at a mean age of 146 days. The experimental design was the entirely randomized, where each sheep represented an experimental unit. The continuous response variables were submitted to analysis of variance and the discrete ones to the Chi-square test. The weight and body condition before mating the sheep, the percentages of pregnancy, calving, gemiparity and losses during gestation, the weight of lambs at birth and the mortality rate until weaning did not differ between groups (P>0.05). White Corriedale ewes presented higher weaning rate of lambs (P